Influence of FIB patterning strategies on the shape of 3D structures: Comparison of experiments with simulations - Rommel, Mathias; Jambreck, J. D.; Ebm, C.; Platzgummer, E.; Bauer, A. J.; Frey, Lothar (Microelectronic Engineering, 2010)
Today's focused ion beam (FIB) systems enable the fast and flexible fabrication of 3D structures with dimensions well below 100 nm. Due to secondary effects like redeposition of sputtered material, however, the fabrication of a targeted shape of the structure is not simple at all. In this work, the influence of the patterning strategy during the sputtering on the shape of a 3D structure with rotational symmetry is studied. Highly different shapes of 3D structures are achieved only due to different rastering strategies or duration times of the ion beam at each raster pixel. The final structure shape can be properly modeled with IonShaper∘ledR simulations. These results clearly prove that the selection of the patterning strategy is the key for appropriate FIB processing of 3D structures. Besides, it is shown that unconventional patterning strategies might enable new types of 3D shapes.
Keywords: FIB; FIB patterning; Focused ion beam; Patterning simulation; Patterning strategy